Constraints Associated to Geographical Indication Usage: Experts and Producers Perspective - Niranjan, D. Alagu; Jha, Sujeet Kumar; Dominic, Ditty Maria; Maiti, Sanjit; Kadian, K. S. (Indian Journal of Extension Education, 2023)
The benefits associated with Geographical Indications (GI) are largely underutilized by most of the registered goods in India, with few exceptions. Therefore, an exploratory study was conducted with experts in the field of GI and also with producers of the GI registered agricultural and food products of Tamil Nadu in order to find reasons for poor GI usage and constraints perceived by the producers of the registered goods. The experts (n=14) reported, lack of awareness among producers about the GI and its benefits, lack of awareness among consumers about the uniqueness and originality of the good, and the absence of quality maintenance mechanism in the registered territory as reasons for poor usage. According to the producers (n=241), lack of awareness, narrow price difference between GI products and their non-GI counterparts and consumer’s preference for low price over quality were the top constraints that pull the producers from using GI.
Keywords: Geographical indications; Benefits; Usage; Experts; Producers; Agricultural; Food